2015
DOI: 10.1002/hpm.2330
|View full text |Cite
|
Sign up to set email alerts
|

Building political will for HIV response: an operational model and strategy options

Abstract: As global programs for HIV response look to transfer responsibility and financing increasingly to country governments, the political will to take on these responsibilities becomes increasingly prominent. However, defining and assessing political will are problematic; it involves intent and motivation, and thus is inherently difficult to observe. It is intimately connected to capacity and is contextually embedded. This article describes an operational model of political will comprised of seven components that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…These findings corroborate that of Quah () who found that Singapore's CPIB is the most effective ACA in the Asian region making major global corruption league tables to rank Singapore as the cleanest country in Asia, in his analysis of ACAs in five countries, including Singapore, Japan, Taiwan, China, and Philippines. The findings in this paper also support the conceptual framework of political will informed by the works of famous scholars (e.g., Brinkerhoff, , ; Brinkerhoff & Kulibaba, ; Kpundeh & Dininio, ; Malena, ). Furthermore, this paper also supports the conclusion drawn by Yeboah‐Assiamah and Alesu‐Dordzi () that political will is the most critical success factor for government anti‐corruption efforts in their research about the calculus of corruption with evidence from Ghana.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…These findings corroborate that of Quah () who found that Singapore's CPIB is the most effective ACA in the Asian region making major global corruption league tables to rank Singapore as the cleanest country in Asia, in his analysis of ACAs in five countries, including Singapore, Japan, Taiwan, China, and Philippines. The findings in this paper also support the conceptual framework of political will informed by the works of famous scholars (e.g., Brinkerhoff, , ; Brinkerhoff & Kulibaba, ; Kpundeh & Dininio, ; Malena, ). Furthermore, this paper also supports the conclusion drawn by Yeboah‐Assiamah and Alesu‐Dordzi () that political will is the most critical success factor for government anti‐corruption efforts in their research about the calculus of corruption with evidence from Ghana.…”
Section: Resultssupporting
confidence: 84%
“…Like any assessment effort, indicators for the four components outlined are wide ranging. However, the paper adopted a similar approach to that of Brinkerhoff who argued that “choices need to be filtered through the principles of what information is necessary and sufficient, but not exhaustive” (Brinkerhoff, , p. 5).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations